Translating knowledge management visions into strategies - Ceruti, Monique; Williams, Angel; Bedford, Denise (Emerald Publishing Limited, 2019)
There is a critical point of failure for every knowledge management effort: when the strategy is isolated from the organization, and when there is no vision anchoring the strategy. This book guides professionals in learning to create a foundation for 21st century knowledge organizations.
Prelims -- Section 1: The Destination Vision of a Knowledge Organization -- 1: Building Knowledge Capacity for a Knowledge Economy -- 2: Knowledge Organizations -- 3: Creating a Vision of the Future -- 4: Translating the Vision INto Strategies -- Section 2: Strategies as Roadmaps -- 5: Knowledge Management Strategies The Big Picture -- 6: Building Your Capacity to Develop the Strategy -- 7: Strategic Affinities and Alignments -- Section 3: Starting the Journey -- 8: Realizing the Vision Moving from Strategy to Tactics -- 9: Defining Roles and Responsibilities to Manage the Strategy -- Section 4: Staying the Course Maintaining the Strategy -- 10: Keeping the Strategy Alive Governance -- Appendix: Developing a Vision and a Strategy A Project Plan Pulling it All Together -- Index.
Includes index.
Print version record.
Keywords: Knowledge management; Business & Economics -- Management; Knowledge management